Students' Word of Mouth Electronic Conversation Formation Model Through Online Service Quality and Students' Online Satisfaction - Salamatun Asakdiyah; Deny Ismanto; Jason Keith Bonaga (West Science Business and Management, 2023)
This study seeks to investigate the impact of E-Service Quality, E-Satisfaction, and the interaction between E-Service Quality and E-Satisfaction on the formation of E-Student Word of Mouth within the Management Study Program at the Faculty of Economics and Business, Ahmad Dahlan University in Yogyakarta. The sample selection involved a combination of convenience sampling and purposive sampling methods. Data collection was accomplished by distributing questionnaires to respondents, addressing aspects of E-Service Quality, E-Satisfaction, and E-WOM. Moderator Regression Analysis (MRA) was employed as the analytical tool. Additionally, T-tests and F-tests were utilized to examine the hypotheses put forth. The results of the partial regression coefficient test using the T-test indicate that both E-Service Quality and E-Satisfaction, as well as their interaction, have a significant influence on E-Student Word of Mouth. Furthermore, the regression coefficient analysis through the F-test demonstrates that the variables E-Service Quality, E-Satisfaction, and their interaction also collectively contribute to the influence on E-WOM. These variables - E-Service Quality, E-Satisfaction, and their interaction - can explain up to 85% of the variance in E-WOM, with the remaining 15% attributed to other variables not included in the research model.